Opportunities for adaptive online collaboration to enhance rural land management. (1st August 2018) - Baumber, Alex; Metternicht, Graciela; Ampt, Peter; Cross, Rebecca; Berry, Emily
Abstract: Cross-property cooperation has the potential to enhance the effectiveness of environmental management actions that cut across property boundaries. Online tools can facilitate this and overcome barriers to landholder engagement in collaborative management. However, collaborative online tools need to be designed and tailored to users' needs and values, and landholder participation in the development process is critical to ensuring uptake and long-term use. This article presents a case study from the Central Tablelands region of New South Wales, Australia, where landholders have been involved in participatory development of a new online collaboration tool. The case study results highlight the significance of issues such as internet access, privacy, technical proficiency and differing stakeholder objectives. A landholder survey identified mapping and the uploading of monitoring data as important functions for the online tool, but these were not rated as highly as functions relating to data security, sharing settings and key term searches. Consequently, we recommend that a future online collaboration tool for the region is not framed specifically as a mapping or citizen science tool, but rather as an adaptive collaboration and communication tool that can incorporate a variety of data types and formats and be modified over time in line with changing landholder needs. Highlights: Online collaboration tools can enhance communication, data-sharing and planning. Mapping and data-sharing are central to participatory mapping and citizen science. Landholders rated privacy, security and ease of use above mapping and data-sharing. There is a need for collaboration tools that are adaptable to changing needs.